SRM analysis for undergratuate courses - Emidio, Bruno Castanho [UNESP]; Junior, Luiz Gonçalves [UNESP]; Creppe, Renato C. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2021)
This work presents a didactic tool for the analysis of switched reluctance motors (SRM) using the finite element method (FEM) and using platforms known and used by undergraduate students as the Finite Element Method (FEMM). The presented method simplifies the observation of magnetic fields, inductances, fluxes and torques and makes the teaching of electromagnetism, electrical machines and power electronics more attractive. Simulation examples applied to SRM type 8/6 and their results such as inductance, torque and flow are presented and discussed.
Keywords: Education; Electric motors; FEMM; SRM; Undergraduate